A New Civic Spirit for Garden City-states: On the Lifework of Sybella Gurney. (November 2018) - Wilson, Matthew
Sybella Gurney (1870–1926) made important and largely unrecognized contributions to British community design theory and practice. This essay begins with an exploration of her youthful social reform activities and academic influences including Leonard Hobhouse, John Ruskin, Auguste Comte, Frederic Le Play, John Stuart Mill, and Ebenezer Howard. These foundational pursuits inspired her to become an ardent cooperator affiliated with the Garden Cities movement and to serve as a sociologist seeking to kindle a "new civic spirit" for post -World War I reconstruction. Gurney, as part of an idealistic circle of thinkers which included Patrick Geddes, considered sociology as a means to realize complete Garden City-states based upon scientific, ethical, and participatory principles.